SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/102804-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Six Key Elements in Integrating People and Technology Toward Quality Achievements of Angsi Field Development Team

Abstract: Angsi is an integrated oil and gas development project in offshore east coast of Peninsular Malaysia. It is one of the biggest oil producers in Malaysia, contributing one-sixth of the total national daily oil production. During its planning and execution stages, the project has had many successes and positive outcomes. It has been recognized as the model of success for all domestic and international operations in PETRONAS Carigali Sdn. Bhd. (PCSB). The uniqueness of achievements in Angsi proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Wax deposition is one of the major problems faced by Malaysian oil and gas industry. Some of the fields in Malaysia such as Penara, Angsi and Dulang are located approximately in a water depth of 60 m to 70 m [8][9][10]. The average seabed temperature for these fields is around 25 °C at depth of 61m whereas the surface temperature is at 34 °C [6,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Wax deposition is one of the major problems faced by Malaysian oil and gas industry. Some of the fields in Malaysia such as Penara, Angsi and Dulang are located approximately in a water depth of 60 m to 70 m [8][9][10]. The average seabed temperature for these fields is around 25 °C at depth of 61m whereas the surface temperature is at 34 °C [6,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that costly remediation measures were incurred due to the multiple formations of hydrate and wax blockage in the North Sea (Staffa field), which led to an abandonment of the Proceedings of the 3 rd Asia Pacific International Conference on Industrial Engineering and Operations Management, Johor Bahru, Malaysia, September 13-15, 2022 © IEOM Society International subsea flowline (Makogon, 2019). Additionally, some Malaysian fields such as Penara, Angsi and Dulang which are located roughly in a water depth of 60m to 70m (Abd Karim, Dahlan, Nordin, & Noor, 2006;Agil, Mohd Saaid, Ibrahim, & Harun, 2008;Kechut, Nadeson, Ahmad, & Raja, 2001), experience wax deposition issues during transportation, in relation to the characteristics of these crude oils, the seabed and surface temperatures and their production histories (Hosseinipour, Japper-Jaafar, & Yusup, 2016).…”
Section: Introductionmentioning
confidence: 99%